Knowledge and acceptance of malaria vaccine among parents of under‐five children of malaria endemic areas in Bangladesh: A cross‐sectional study - Mohammad Ashraful Amin; Sadia Afrin; Atia S. Bonna; Md Faisal K. Rozars; Mohammad Hayatun Nabi; Mohammad Delwer H. Hawlader (Wiley, 2023)
Abstract Background Malaria exists as an endemic in many countries including Bangladesh and the malaria vaccine is not yet available here. The study aimed to assess the level of knowledge and acceptance of the malaria vaccination among the parents of children under the age of five in Bangladesh's malaria‐endemic areas and the sociodemographic, behavioural, and household factors associated with the acceptance and knowledge of the malaria vaccine. Methods From January to March 2022, a cross‐sectional study was conducted in all five malaria‐endemic districts of Bangladesh, involving 405 parents of children under the age of 5 who met the inclusion criteria. Multiple logistic regression was used to analyze the factor affecting parents' acceptance and knowledge of malaria vaccination in children under five and other variables. Results Majority (54%) of the respondents were mothers. Almost half (49%) of the respondents were aged between 26 and 35 years old and around 90% were from rural areas. A small portion (20%) of the participants were housewives and 46% of them completed primary education. Overall, 70% of the study participants reported that they would accept malaria vaccination independently. About one‐fourth (25%) heard about the malaria vaccine and 48% of them mentioned health professionals as the source of information. Knowledge of malaria vaccination was found associated with residence, income, and family size. Acceptance and knowledge were both associated with residence, education, occupation, income, and family size. In a multivariable analysis, housing structure, house wall, house window, knowledge of malaria, testing for malaria, and being diagnosed with malaria were all associated with knowledge of and acceptance of getting vaccinated against malaria. Conclusions The present study highlights the necessity of creating awareness of malaria vaccines in epidemic areas of Bangladesh. This study offers crucial data to develop a policy for a novel malaria vaccine, supporting its adoption in Bangladesh. Public Contribution This study was based on interviews. The interviewees were recruited as public representatives from the malaria‐endemic area to assist us in building an understanding of knowledge and acceptance of the malaria vaccine among parents of under‐five children in Bangladesh.